Exploring Spatially Varying Relationships Between Preterm Birth and Socioeconomic, Demographic, and Behavioral Factors in Georgia, USA Using Geographically Weighted Logistic Regression. (31st May 2021) - Tu, Jun; Tu, Wei
Abstract: Preterm birth (PTB) is an important cause of infant morbidity and mortality around the world. A good understanding of its associations with relevant factors is essential for an effective reduction in PTB risk. This study explores the spatially varying relationships between PTB and demographic, socioeconomic, and behavioral factors in the state of Georgia, USA using Geographically Weighted Logistic Regression (GWLR). The results show the relationships between PTB and factors vary over space, and the spatial patterns in the varying relationships are related to the socioeconomic and urbanization characteristics of the communities where the births were located. For example, PTB has significant positive relationships with black mothers and single mothers, and significant negative relationships with maternal education in the majority of Georgia, but such relationships are insignificant in small portions of rural Georgia with low socioeconomic status (SES). PTB has significant positive relationships with maternal age and parity, and significant negative relationships with female births in small portions of Georgia, particularly in the Atlanta Metropolitan Area, while in larger portions of rural Georgia with overall low SES, those relationships are not significant. Thus, health prevention and intervention policies should be tailored to address the locally important factors to reduce PTB risk.